pEl1573 Carrying bla(IMP-4), from Sydney, Australia, Is Closely Related to Other IncL/M Plasmids - Partridge, Sally R. (American Society for Microbiology, 2012)
Complete sequencing of pEl1573, a representative IncL/M plasmid carrying bla(IMP-4) from Sydney, Australia, revealed an ∼60-kb backbone almost identical to those of IncL/M plasmids pCTX-M3, from Poland, and pCTX-M360, from China, and less closely related to pNDM-HK, pOXA-48a, and pEL60, suggesting different lineages. The ∼28-kb Tn2-derived multiresistance region in pEl1573 is inserted in the same location as those in pCTX-M3 and pNDM-HK and shares some of the same components but has undergone rearrangements.